1987
DOI: 10.1055/s-2008-1050441
|View full text |Cite
|
Sign up to set email alerts
|

Die Lymphdrainage von Cornea, Limbus und Conjunctiva*

Abstract: Air (n = 30), patent blue (n = 30), Berlin blue (n = 30), Berlin blue and air (n = 30), and Berlin blue and Mercox (n = 30) were injected into the corneas and conjunctivas of 150 enucleated cattle eyes. Using air for injection, so-called Bowman "corneal tubes" form in the cornea, which can easily be filled with pigment (patent blue, Berlin blue). In some cases (n = 3) the conjunctival lymphatics were filled with air during injection into the cornea. Besides the "corneal tubes", larger vessel-like structures ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Up to 50 per cent of the total amount of a topically applied low molecular weight drug is absorbed through the conjunctiva into the subconjunctival connective tissue 187 , 188 . This tissue contains a dense net of blood and lymph vessels, 189 , 190 which rapidly drain topically applied drugs into the regional lymphatics and vasculature before they reach the sclera 32 , 191 . Hydrophilic drug penetration through the sclera is very similar to penetration through the corneal stroma: permeability decreases in a linear fashion for molecules between 280 Da and 40 kDa, followed by a very rapid drop in permeability for larger molecules 192 , 193 , 194…”
Section: Topical or Local Drug Delivery To The Eyementioning
confidence: 99%
“…Up to 50 per cent of the total amount of a topically applied low molecular weight drug is absorbed through the conjunctiva into the subconjunctival connective tissue 187 , 188 . This tissue contains a dense net of blood and lymph vessels, 189 , 190 which rapidly drain topically applied drugs into the regional lymphatics and vasculature before they reach the sclera 32 , 191 . Hydrophilic drug penetration through the sclera is very similar to penetration through the corneal stroma: permeability decreases in a linear fashion for molecules between 280 Da and 40 kDa, followed by a very rapid drop in permeability for larger molecules 192 , 193 , 194…”
Section: Topical or Local Drug Delivery To The Eyementioning
confidence: 99%
“…Stereomicroscopic research on the cornea, limbus and the lymph vessels in the conjunctiva of cattle revealed that there were no valves or invaginations in the lymphatic vessels, while there were diverticula's like humps in the vessels (Gruntzig, Nolte, Schad, & Pfankuchen, ). However, according to Guo et al (), there were cover‐like formations in the conjunctiva of monkeys.…”
Section: Introductionmentioning
confidence: 99%